A checklist of endemic plants on the Korean Peninsula II - Gyu Young Chung; Hyun-do Jang; Kae Sun Chang; Hyeok Jae Choi (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2023)
Following recent taxonomic, distributional, and nomenclatural revisions, an updated checklist of endemic plants on the Korean Peninsula is needed. This study provides an updated checklist of vascular plants endemic to the Korean Peninsula and describes their distribution within administrative provinces. The revised checklist includes 373 endemic taxa (304 species, six subspecies, 49 varieties, and 14 nothospecies) from 179 genera and 64 families, representing 9.5% of the total native flora of the Korean Peninsula. Asteraceae (41 taxa), Ranunculaceae (29 taxa), Liliaceae s.l. (24 taxa), and Rosaceae (22 taxa) were the most widely represented families. Compared with the most recent checklist published in 2017, 39 taxa were excluded from the checklist; one taxon was excluded because it did not have a valid published name, seven taxa were excluded because their natural habitats extended to neighboring countries, four taxa were excluded because they were treated as a rank form, and 27 taxa were excluded because they had been identified as heterotypic synonyms of taxa distributed outside of the Korean Peninsula. Fifty-two new taxa were included based on the literature. This checklist will help to focus conservation efforts and provide a framework for research, protection, and policy implementation related to these endemic taxa.